(untitled) (Journal of Economic Research & Business Administration, 2020)
This article sets out the author’s position on the possibility of using integrated accounts in crop production to keep track of the costs of agricultural activities in the industry in order to help the administration in making effective management decisions. The aim of the study is to develop a system of analytical accounts for the process accounting of production costs of the crop industry. The methodological basis of the work was general scientific principles and research methods: analytical, logical, monographic methods, as well as groupings and comparisons. From the perspective of an integrated approach, the article used the research of modern scientists in the field of managerial accounting in agricultural enterprises, as a result, the author developed and presented the structure of the codes of the system of accounts for cost accounting, the analytical levels in the application of the normative cost accounting system in grain production, the classification of industry costs for variables and fixed elements, as well as codes of accounts of deviation accounting for monitoring the execution of estimates for the purposes of management accounting eta. The results of the study are of theoretical and practical significance and can be recommended for use in the organization of management accounting in grain production, and the same showed that grain production is of strategic importance for ensuring the economic security of the state, therefore, great attention should be paid to the key problems of increasing its efficiency – increasing production grain and improve its quality. It is concluded that the application of the proposed system of synthetic and analytical cost accounting for agrotechnical measures will provide more detailed information about each responsibility center, which in the future will significantly help in making managerial decisions aimed at improving the efficiency of grain farms